Solve Using the Square Root Property 5x^2-x-50=2(2x^2+3)

Math
5×2-x-50=2(2×2+3)
Simplify 2(2×2+3).
Tap for more steps…
Apply the distributive property.
5×2-x-50=2(2×2)+2⋅3
Multiply.
Tap for more steps…
Multiply 2 by 2.
5×2-x-50=4×2+2⋅3
Multiply 2 by 3.
5×2-x-50=4×2+6
5×2-x-50=4×2+6
5×2-x-50=4×2+6
Move all terms containing x to the left side of the equation.
Tap for more steps…
Subtract 4×2 from both sides of the equation.
5×2-x-50-4×2=6
Subtract 4×2 from 5×2.
x2-x-50=6
x2-x-50=6
Move 6 to the left side of the equation by subtracting it from both sides.
x2-x-50-6=0
Subtract 6 from -50.
x2-x-56=0
Factor x2-x-56 using the AC method.
Tap for more steps…
Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -56 and whose sum is -1.
-8,7
Write the factored form using these integers.
(x-8)(x+7)=0
(x-8)(x+7)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
x-8=0
x+7=0
Set the first factor equal to 0 and solve.
Tap for more steps…
Set the first factor equal to 0.
x-8=0
Add 8 to both sides of the equation.
x=8
x=8
Set the next factor equal to 0 and solve.
Tap for more steps…
Set the next factor equal to 0.
x+7=0
Subtract 7 from both sides of the equation.
x=-7
x=-7
The final solution is all the values that make (x-8)(x+7)=0 true.
x=8,-7
Solve Using the Square Root Property 5x^2-x-50=2(2x^2+3)

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top